Citrullus collocynthis Extract as Corrosion inhibitor for carbon low steel in Acid Medium using Weight Loss Method - Al-Jabery, Rasha.N. (University of Thi-Qar Journal of Science, 2014)
corrosion inhibition of carbon low steel using methanol extract of the fruits of Citrullus collocynthis was studied using weight loss measurement at 303,323 and 333ºK. The inhibition efficiency increased with the increase in inhibitor concentration but decreased with temperature. The Langmuir adsorption isotherm was tested for their fit to the experimental data . The apparent activation energies ,entropies of the dissolution process and the free energies for the adsorption process were determined an discussed .All computed quantum chemical parameters are found to correlate well with experimental inhibition efficiency of inhibitor